Truth as one and many - Lynch, Michael P. (Michael Patrick), 1966- (Oxford : Oxford University Press, 2009)
What is truth? Michael Lynch defends a bold new answer to this question. Traditional theories hold that all truths are true in the same way. More recent theories claim that the concept of truth is of no real importance. Lynch argues against both these extremes: truth is a functional property whose function can be performed in more than one way.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Truth